Public policies for promoting innovation and reactivation of the publishing sector in Ecuador - Jaramillo Escobar, Bladimir Heriberto (Scripta Mundi, 2022)
The economic crisis in which all the economies of the world find themselves as a consequence of the Covid 19 pandemic and the complex geopolitical panorama due to the war between Russia and Ukraine, since the beginning of 2022, have significantly affected the cultural industry in the Ecuador and particularly the publishing sector. This one is in serious troubles. For that reason, toknow its structure, the contribution it provides to the Ecuadorian society and to analyze the main public policies implemented for the reactivation of the publishing sector during the last five years are the objectives of this exploratory and descriptive research work. It is based on bibliographic information compiled from mainly secondary sources, due to the limited dissemination of official data and the difficulties in finding them. A survey was carried out on university students to find out their investment of time in reading.The data was compared with that of other organisms. Among the main conclusions, the low reading level of Ecuadorians, the limited public policies for the sector and the little innovation incorporated in the book production processes are reaffirmed. A set of recommendations that could help the reactivation of the Ecuadorian publishing sector are proposed.
Keywords: public policies; publishing sector; independent publishers; editorial innovation; conomic recovery